Experimental analysis of propagation regimes during the autoignition of a fully premixed methane–air mixture in the presence of temperature inhomogeneities - Strozzi, Camille; Mura, Arnaud; Sotton, Julien; Bellenoue, Marc (Combustion and flame, 2012)
The present work is devoted to the study of the combustion processes of a homogeneous methane–air mixture subject to thermal stratification within a rapid compression machine (RCM). Temperature fields obtained in nonreactive conditions have been documented in a previous study and the present work aims at correlating these data with the combustion process. The analysis of chemiluminescence images enables the delineation of two propagation regimes, namely spontaneous ignition fronts and deflagrations. The first is observed for short ignition delays, as the fluid features a fairly large and homogeneous hot core zone. The second dominates the combustion process for longer ignition delays. Indeed, despite global homogenization of the temperature fields, the hottest zones are fairly narrow and surrounded by non-negligible thermal gradients, which favors the formation of deflagration. The results thus clearly show a strong correlation between the preignition temperature field and the subsequent combustion process. They are commented on in the light of recent literature. In a second part, quantitative predictions of the occurrence of autoignition fronts and deflagrations are performed by employing a criterion derived from the analysis of direct numerical simulation data (Sankaran et al., 2005). The results are in good agreement with others previously obtained through chemiluminescence imaging for early and intermediate stages of combustion. It is more difficult to reach definitive conclusions for later instants. The present work highlights the relevance but also suggests some limitations of the corresponding criterion for the analysis of homogeneous charge compression ignition (HCCI) combustion processes at the cylinder scale. Furthermore, the quantitative data gathered within the RCM demonstrate the relevance of this device for further investigation of these fundamental issues.